City of Rents: The limits to the Barcelona model of urban competitiveness. (12th November 2013) - Charnock, Greig; Purcell, Thomas F.; Ribera‐Fumaz, Ramon
Abstract The turn towards the knowledge‐based economy and creative strategies to enhance urban competitiveness within it has been well documented. Yet too little has been said to date about the transformation of land use for new productive activities, and the contradictions inherent to this process. Our case study is Barcelona, an erstwhile 'model' for urban regeneration which has sought to transform itself into a global knowledge city since 2000. Through the lens of Marxian value theory, and Harvey's writing on urban monopoly rents especially, we show how the 22@Barcelona project — conceived with received wisdom about the determinants of urban knowledge‐based competitiveness in mind — amounted to an exercise in the capture of monopoly rents, driven by the compulsion of public sector institutions, financiers and developers to pursue rental profit‐maximizing opportunities through the mobilization of land as a financial asset.